Nihilisme Normatif Kontemporer: Studi Kritis terhadap Anti Otoritas dalam Memahami Teks Islam: Contemporary Normative Nihilism: A Critical Study on Anti-Authority in Understanding Islamic Text (Nash) - Fatha, Hijriy; Rahmat , Sylmawan (Journal of Islamic and Occidental Studies, 2024)
In the field of philosophy, the concept of nihilism has developed, namely a conception that denies all existing values and norms. Thus, this gives rise to the understanding of the relativity of truth. This ideology assumes that there is no absolute truth. All current statements and understandings are not necessarily true and may very well be wrong, including the interpretations of Islamic scholars towards Islamic religious texts. This understanding is used as justification for everyone who wants to interpret religious texts as they wish. Of course, this is very contrary to the wisdom of the ulama. Adherents of this understanding equate the Qur'an with other texts to the point of calling the Qur'an a cultural product and historical text.